Systemy relacji między państwem a kościołami i związkami wyznaniowymi - Gołda-Sobczak, Maria (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The systems and models of relationship which are presented lead to a unanimous conclusion that the present globalizing world leaves no room for intolerance; however, the integrist and fundamentalist tendencies keep reviving. The concept of civic society, the state of law, the standards of the EU and Council of Europe provide a clear indication for states to develop such relations with respect to the law on religious denomination that will prevent religious minorities from being, or feeling, discriminated against. The establishment of standards which are friendly for all churches and religious associations is only the beginning, though. The next stage involves political activity and the interpretation of the regulations allowing for the elimination of discrimination from the realm of actual relations.